A rising thunder : from Lincoln's election to the Battle of Bull Run : an eyewitness history - Wheeler, Richard, 1922-2008. (New York, NY : HarperCollins, 1994)
In this book Wheeler describes the tumultuous events that preceded and led up to the outbreak of the war, beginning before Lincoln's election. He follows the conflict of words among abolitionists, those who would preserve the Union at all costs, and the defenders of slavery and states' rights; the confused jockeying of the political parties in the months before the 1860 election to find the most suitable candidates and platforms for them to run on; and, of course, the.
efforts of the new president, Abraham Lincoln, to maneuver through the shoals of turmoil. When all efforts to avoid a final break fail, the narrative reaches a climax with the Confederate assault on Fort Sumter, followed by the first major battle at Bull Run, a blood-letting that shattered the hopes and beliefs of those on both sides who had somehow expected a quick and easy war.
Includes bibliographical references (p. 397-400) and index.
Keywords: United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Fort Sumter (Charleston, S.C.) -- Siege, 1861.; Bull Run, 1st Battle of, Va., 1861.